The neurogenic genes egghead and brainiac define a novel signaling pathway essential for epithelial morphogenesis during Drosophila oogenesis. - Goode, S.; Melnick, M.; Chou, T.B.; Perrimon, N. (Development, 1996)
Notch (N) and other neurogenic genes have been implicated in two fundamental processes, lateral specification of cell fates, and epithelial development. Previous studies have suggested that the neurogenic gene brainiac (brn) is specifically required for epithelial development (Goode, S., Morgan, M., Liang, Y-P. and Mahowald, A. P. (1996). Dev. Biol. 178, 35-50). In this report we show that egghead (egh), a gene with phenotypes identical to brn, encodes for a novel, putative secreted or transmembrane protein. We describe the role of egh and brn germline function in the morphogenesis of the follicular epithelium from the time it is born through the time that it migrates towards the oocyte late in oogenesis. By comparing the function of germline egh and brn to N during oogenesis, we have obtained direct evidence for the involvement of Notch in maintenance of the follicle cell epithelium, and the specificity of brn and egh in epithelial development during oogenesis. The most striking phenotype observed for all three genes is a loss of apical-basal polarity and accumulation of follicular epithelial cells in multiple layers around the oocyte. The spatiotemporal onset of this adenoma-like phenotype correlates with the differential accumulation of egh transcripts in the oocyte at stage 4 of oogenesis. In contrast to N, we find that brn and egh are essential for the organization, but not specification, of stalk and polar cells. The expression patterns and functional requirements of brn, egh, and N lead us to propose that these genes mediate follicular morphogenesis by regulating germline-follicle cell adhesion. This proposal offers explanations for (1) the involvement of egh and brn in N-mediated epithelial development, but not lateral specification, (2) why brn and egh embryonic neurogenic phenotypes are not as severe as N phenotypes, and (3) how egh and brn influence Egfr-mediated processes. The correlation between the differential expression of egh in the oocyte and the differential requirement for brn, egh, and N in maintaining the follicular epithelium around the oocyte, suggests that Egghead is a critical component of a differential oocyte-follicle cell adhesive system.